The mediating role of motivation types in employees’ organizational commitment and perceived leadership styles relationship - Türker, Mine (My University, 2013)
ÇALIŞANLARIN ÖRGÜTE BAĞLILIKLARI VE ALGILANAN LİDERLİK TARZLARI İLİŞKİSİNDE GÜDÜLENME SEVİYELERİNİN ARA DEĞİŞKEN ROLÜ Bu çalışmanın amacı, çalışanın örgütle kurduğu psikolojik bağı yansıtan örgüte bağlılıkları ile algıladıkları liderlik tarzları ilişkisinde güdülenme seviyelerinin ara değişken rolünü ve ayrıca kişi-iş uyumu değişkeninin, algılanan liderlik tarzı- güdülenme seviyeleri ilişkisinde şartlı değişken rolünü incelenmektedir. Güdülenme, kendini yönetme özerkliği teorisi çerçevesinde ele alınarak, farklı özerkliğe sahip güdülenme seviyelerinin incelenmesine olanak tanımıştır. Kendini yönetme özerkliği teorisi, güdülenmenin işyeri dahil yaşamın pek çok alanında uygulamaları olmasını sağlayan farklı bir yaklaşımdır. Bu çalışma, %58,75’lik geri dönüş oranı ile denizcilik sektöründe çalışan 470 kişiye uygulanmıştır. Araştırma sonucunda güdülenme seviyelerinden sadece özerk güdülenme ve güdülenmeme için kısmi ara değişken rolü gözlenmiştir; kişi-iş uyumu için şartlı değişken rolü gözlenmemiştir. Özerk güdülenme, otoriter liderlik - içselleştirilmiş bağlılık ilişkisinde; güdülenmeme ise serbest bırakıcı liderlik - zorunlu bağlılık ilişkisinde kısmi ara değişken rolü oynamıştır.

THE MEDIATING ROLE OF MOTIVATION TYPES IN EMPLOYEES’ ORGANIZATIONAL COMMITMENT AND PERCEIVED LEADERSHIP STYLES RELATIONSHIP The purpose of this study is to examine the mediator role of self-determined motivation types in the relationship between perceived leadership styles and employees’ organizational commitment, which refers to the psychological bond between individual and organization. Self-determination theory is a welcomed approach of human motivation in work motivation area which varies extrinsic motivation in differing degrees of internalization and by this way makes it applicable to a variety of life domains including workplace. Also person-job fit is included as moderator variable to examine the interaction with perceived leadership style in its relation to employee motivation. Data gathered from 470 seaman who work for Turkish shipping companies, with a response rate %58,75. According to the results, the mediator role of self-determined motivation is partially supported. Autonomous motivation partially mediated authoritarian leadership and internalized commitment relationship and amotivation partially mediated laissez-faire leadership and lack of alternatives relationship. But there is no moderator effect observed for person-job fit.
Keywords: Örgüt Kültürü; Örgütsel Bağlılık